1996
DOI: 10.1113/expphysiol.1996.sp003978
|View full text |Cite
|
Sign up to set email alerts
|

The influence of age on the assessment of motor unit activation in a human hand muscle

Abstract: SUMMARYTwo indices of motor unit recruitment, the ramp-force and repetitive-discharge thresholds, were compared in the first dorsal interosseus muscle of ten young and twelve elderly subjects. The purpose was to determine the effect of age on the relationship between the two recruitment thresholds and the spike-triggered average force of motor units. Each subject performed three tasks requiring isometric abduction of the left index finger: a maximum voluntary contraction (MVC), a ramp-and-hold contraction, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 20 publications
3
48
1
Order By: Relevance
“…Appearance of a decline in tension from 21/22 to 27 mo of age for type FF and FR units might indicate that the capture of extra-muscle fibers and the subsequent recovery of the contractile function of reinnervated muscle fibers take time to overwhelm the effects of atrophy and a decrease in specific tension. This remodeling of the motor units may be related to findings of Masakado et al (1994), who reported that the variance in the relationship between the motor-unit tension and recruitment threshold was greater in the elderly subject compared with younger ones (but see also Spiegel et al 1996). Erim et al (1999) also observed a disturbance of the onionskin phenomenon in the relationship between firing rate and recruitment threshold in a human muscle.…”
Section: Discussionmentioning
confidence: 68%
“…Appearance of a decline in tension from 21/22 to 27 mo of age for type FF and FR units might indicate that the capture of extra-muscle fibers and the subsequent recovery of the contractile function of reinnervated muscle fibers take time to overwhelm the effects of atrophy and a decrease in specific tension. This remodeling of the motor units may be related to findings of Masakado et al (1994), who reported that the variance in the relationship between the motor-unit tension and recruitment threshold was greater in the elderly subject compared with younger ones (but see also Spiegel et al 1996). Erim et al (1999) also observed a disturbance of the onionskin phenomenon in the relationship between firing rate and recruitment threshold in a human muscle.…”
Section: Discussionmentioning
confidence: 68%
“…For example, in-phase modulation of percent power in the interference EMG of the agonist and antagonist muscles would increase coactivation, thereby stiffening the joint and reducing the fluctuations in acceleration (19,31). There is evidence that old adults exhibit increased coactivation during slow abduction-adduction movements of the index finger (1,24,35). Furthermore, the broader peak in the power spectrum for the old adults (50-125 Hz vs. 25-50 Hz) likely reduced phase differences between the frequency components of the signal (28) and resulted in less alternating activation between the agonist and antagonist muscles.…”
Section: Discussionmentioning
confidence: 99%
“…We did this because there is evidence that force variability increases with contraction speed (Christou and Carlton 2002;Poston et al 2010). In addition, previous work suggests that older adults exhibit a faster rate of force release than young adults and compared with force increase (Spiegel et al 1996). Thus, constraining the rate of force provided a more fair comparison of the capacity of young and older adults to control force for the two phases.…”
Section: )mentioning
confidence: 99%
“…This finding seemed to be independent of the participant's age or rate of force generation. Another study involving isometric contractions of the first dorsal interosseous muscle demonstrated that older adults exhibited more difficulty during the release force phase of the task (Spiegel et al 1996). In both studies, the rate of force increase and release was not controlled.…”
mentioning
confidence: 98%